Axially adjustable magnetic properties in arrays of multilayered Ni/Cu nanowires with variable segment sizes. (July 2016) - Shirazi Tehrani, A.; Almasi Kashi, M.; Ramazani, A.; Montazer, A.H.
Abstract: Arrays of multilayered Ni/Cu nanowires (NWs) with variable segment sizes were fabricated into anodic aluminum oxide templates using a pulsed electrodeposition method in a single bath for designated potential pulse times. Increasing the pulse time between 0.125 and 2 s in the electrodeposition of Ni enabled the formation of segments with thicknesses ranging from 25 to 280 nm and 10–110 nm in 42 and 65 nm diameter NWs, respectively, leading to disk-shaped, rod-shaped and/or near wire-shaped geometries. Using hysteresis loop measurements at room temperature, the axial and perpendicular magnetic properties were investigated. Regardless of the segment geometry, the axial coercivity and squareness significantly increased with increasing Ni segment thickness, in agreement with a decrease in calculated demagnetizing factors along the NW length. On the contrary, the perpendicular magnetic properties were found to be independent of the pulse times, indicating a competition between the intrawire interactions and the shape demagnetizing field. Graphical abstract: Highlights: Fabrication of multilayered Ni/Cu nanowires by a pulsed alternating current method. Using designated pulse times, segments with different geometries were created. Investigation of morphologies, crystalline characteristics and magnetic properties. Obtaining adjustable magnetic coercivity and squareness in the axial direction. Correlating the axial magnetic properties with calculated demagnetizing factors.